The Distribution of Radioiodine-Labeled N-Isopropyl-plodoamphetamine in Permanently Ischemic Brain of the Mongolian Gerbil - Jinnouchi, S.; Hoshi, H.; Watanabe, K.; Ueda, T.; Yamaguchi, T. (Nuklearmedizin - NuclearMedicine, 1988)
In a study of the distribution of N-isopropyl-p-131l-iodoamphetamine (IMP) in the permanently ischemic brain of 35 mongolian gerbils, the right common carotid artery was ligated under ether anesthesia. After given time intervals, MBq (50μCi) of IMP was injected into 17 gerbils which had severe neurological symptoms, and into 3 normal gerbils for controls. One minute there after each gerbil was sacrified and brain autoradiography was performed. The activity of IMP in various parts of the brain was calculated from each autoradiogram. Low perfusion areas were observed in the right cerebral hemisphere and the brain stem (5-25% of normal value) from the first minute up to 24 h after ligation. In addition, low perfusion areas were also observed in the left cerebral hemisphere (40-60% of normal value) which represented a remote effect. These results suggest the usefulness of IMP for demonstrating cerebral ischemia and diaschisis.Die Verteilung von Isopropyl-p- 131J-Jodamphetamin (IMP) wurde im ischämischen Hirn von 35 mongolischen Wüstenmäusen untersucht. Nach Ligatur der rechten A. carotis communis unter Ätheranästhesie wurden, in definierten Zeitabständen, 1,35 MBq (50 μCi) IMP injiziert. Untersucht wurden 17 Tiere mit schweren neurologischen Ausfällen und drei Kontrolliere. Eine Minute nach der Injektion wurden die Tiere getötet und das Gehirn autoradiographisch untersucht. Aus jedem Autoradiogramm wurde die IMP-Anreicherung in den verschiedenen Hirnregionen berechnet. Eine Minute bis 24 h nach der Ligatur fanden sich Niederflußareale in der rechten Hemisphäre und im Hirnstamm (5-25% des Normalwertes). Zusätzlich wurde eine beglei tende Minderperfusion der linken Hemisphäre (40-60%) nachgewiesen. Die Ergebnisse belegen die Brauchbarkeit von IMP für den Nachweis einer zerebralen Ischämie bzw. Diachisis.